USING WORD TO SENTENCE BINGO INTEGRATED WITH COMPUTER TO IMPROVE STUDENTS’ SPEAKING ABILITY - Lina Satriyani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Lately, the strengthening role of English within multilingual societies has led changes which urged teachers to use innovative ways in teaching in order to prepare students to be a better communicator. ICT has been known as potentially powerful enabling tools for creating that innovation. One good example is by using Word to Sentence (WtS) Bingo board integrated with computer to play a game in improving junior high school students’ speaking skills in fluency and accuracy. This game is played by students in groups. Each group has their own board (5x5), two sets of cards (12 nouns and 13 verbs), and a marker. They stick each of the words freely. Then, they have to mark every word mentioned by the computer as the ‘word caller’. To get the score the group is required to create sentences orally as many as they can in two minutes at the time they say ‘BINGO’ whenever the marked words create a line diagonally or vertically or horizontally. Last, they have to compose a short text by using some sentences they have made before. The winner is the group who gets the highest score. The computer is used as the ‘word caller’ in order to help students in giving the model of pronouncing the words correctly and make the game more interesting. Through this way they can practice what they have learned cooperatively so they have more confidence to speak in more relaxed and enjoyable atmosphere.